Management of Cucurbit Downy Mildew in Florida - Mason J. Newark; Matthews L. Paret; Nicholas S. Dufault; Pamela D. Roberts; Shouan Zhang; Gary E. Vallad; Joshua H. Freeman; Eugene McAvoy (EDIS)
Cucurbit downy mildew is a major disease that affects over 40 species of cucurbits, like watermelon, muskmelon, cucumber, squash, and pumpkin. The classic sign of the disease is the presence of dark sporangia, a structure that holds developing spores, on the underside of infected leaves. As the disease progresses, it may lead to large necrotic areas that cause defoliation and a reduction of yield and marketable fruit. This nine-page fact sheet describes the symptoms and signs, epidemiology and disease cycle, host range and pathotypes, and the ways to manage cucurbit downy mildew. Written by Mason J. Newark, Mathews L. Paret, Nicholas S. Dufault, Pamela D. Roberts, Shouan Zhang, Gary E. Vallad, Josh Freeman, and Gene McAvoy, and published by the Plant Pathology Department. http://edis.ifas.ufl.edu/pp325